4‐Acetylthio‐2, 2‐dimethyl‐3‐oxobutyl Group as an Esterase‐ and Thermo‐Labile Protecting Group for Oligomeric Phosphodiesters. Issue 26 (1st August 2014) - Leisvuori, Anna; Lönnberg, Harri; Ora, Mikko
Abstract: (4‐Acetylthio‐2, 2‐dimethyl‐3‐oxobutyl)‐protected oligomeric phosphodiesters1 and2 were synthesized and removal of the protecting groups in the presence and absence of hog liver esterase was followed at pH 7.5 and 37 °C. Phosphotriesters1 and2 were successfully converted into the desired fully deprotected phosphodiesters3 and4, respectively. Some cleavage of internucleosidic P–O bonds took place, which reduced the yield of3 and4 . Non‐enzymatic removal of the protecting group was only modestly retarded by accumulation of negative charge on the molecule. With1, the half‐lives for the departure of the first and second protecting groups were 7.8 and 10.7 h, respectively, and with2, 6.2 and 7.2 h, respectively. After 4 d, 70 % of both starting materials1 and2 were converted into the unprotected phosphodiester. The presence of hog liver esterase (2.6 units mL –1 ) resulted in fast removal of the first protecting group (τ1/2 2.7 min and 36 min with1 and2, respectively), but the appearance of fully deprotected3 and4 was accelerated only by a factor of 2, consistent with dramatic retardation of the enzymatic reaction upon accumulation of the negative charge. Abstract : Thymidine‐derived trimers and tetramers that bear three enzymolabile and thermolabile 4‐acetylthio‐2, 2‐dimethyl‐3‐oxobutyl groups undergo conversion to fully deprotected phosphodiesters at pH 7.5 and 37 °C in the presence and absence of enzyme. Some degradation of the phosphate backbone takes place as a side reaction.